2007
DOI: 10.1016/j.jtcvs.2006.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ischemic time on survival after heart transplantation varies by donor age: An analysis of the United Network for Organ Sharing database

Abstract: The effect of ischemic time on survival after heart transplantation is dependent on donor age, with greater tolerance for prolonged ischemic times among grafts from younger donors. Both donor age and anticipated ischemic time must be considered when assessing a potential donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
152
3
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(181 citation statements)
references
References 8 publications
11
152
3
15
Order By: Relevance
“…Differences in pre-HT risk of graft loss could have played a role in graft outcomes between SF and MS groups; however, we found no difference in graft or patient survival based on MS use in multivariable analysis. Variables other than MS that we found to be independent risk factors for graft loss have been shown to be independent risk factors in previous studies (4)(5)(6)(7)(8), The results of our multivariable model were confirmed by our propensity-matched analysis, which similarly showed that there is no graft or patient survival advantage to the use of MS. Propensity-matched analysis did not show that induction therapy influenced outcomes or that a combination of induction therapy or no induction with or without MS use made a difference in graft outcomes, which is consistent with data from the International Society for Heart and Lung Transplantation registry (1). However, we did not differentiate between the type of induction agent used and it is not known whether any combination of a particular induction agent with an MS or SF regimen would affect graft outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…Differences in pre-HT risk of graft loss could have played a role in graft outcomes between SF and MS groups; however, we found no difference in graft or patient survival based on MS use in multivariable analysis. Variables other than MS that we found to be independent risk factors for graft loss have been shown to be independent risk factors in previous studies (4)(5)(6)(7)(8), The results of our multivariable model were confirmed by our propensity-matched analysis, which similarly showed that there is no graft or patient survival advantage to the use of MS. Propensity-matched analysis did not show that induction therapy influenced outcomes or that a combination of induction therapy or no induction with or without MS use made a difference in graft outcomes, which is consistent with data from the International Society for Heart and Lung Transplantation registry (1). However, we did not differentiate between the type of induction agent used and it is not known whether any combination of a particular induction agent with an MS or SF regimen would affect graft outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…The relationship between prolonged allograft ischemic time and reduced survival after heart transplantation has been clearly demonstrated (47,48), although this effect appears to be modified by donor age. This observation, which has constrained distant organ procurement, stimulated the development of technologies for continuous ex vivo perfusion of donor hearts (49).…”
Section: Ex-vivo Cardiac Perfusionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16] Current donor and recipient criteria limit the use of hearts to donors who are within approximately 20% of the recipient's weight or a DR weight ratio of 0.8 to 1.2. Previous studies analyzing the impact of donor-to-recipient size have done so from an institutional perspective or as a subanalysis of a larger study.…”
Section: Patel Et Al Dr Weight Ratio and Htx S85mentioning
confidence: 99%
“…1 Because of the donor organ deficit, efforts have been made to use marginal donors in an attempt to increase the donor organ pool and reduce waiting list mortality. [2][3][4][5][6][7] These attempts include the use of hearts from older donors 8 -11 and hearts that have been subjected to longer ischemic times, [12][13][14][15][16] both of which have led to conflicting results in the literature.…”
mentioning
confidence: 99%